2019
DOI: 10.1055/s-0039-1692310
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nervous System Derangement as a Predictor of Cardiovascular Disease in Obese Postmenopausal Women

Abstract: Background and Aim Cardiovascular disease is more prevalent in women after menopause and particularly in those aged > 60 years. Obesity during menopause has become a growing cause of concern as the source of estrogen during this period is extragonadal. Autonomic function tests serve as effective markers of autonomic activity. Any derangement of autonomic functions in obese postmenopausal women would serve as an early marker for the detection of cardiovascular disease. The aims and objectives of this study were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In a study done by M Taranikatti et al, they have concluded that postmenopausal women with obesity suffer from autonomic derangements and are possibly at an increased risk of developing heart disease. 12 Arunima Chaudhuri et al, studied anatomic function and obesity in postmenopausal women, reported that decreased sympathovagal activity with obesity in postmenopausal women. 13 Our study shows that, there is a similar enhanced risk of CVDs in post menopausal women, all the more with greater risk in the patients having diabetes as there is an established relation between Autonomic nervous system dysfunction in the form of heart rate variability and postural variations in blood pressure and cardiovascular events which cause high degree morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done by M Taranikatti et al, they have concluded that postmenopausal women with obesity suffer from autonomic derangements and are possibly at an increased risk of developing heart disease. 12 Arunima Chaudhuri et al, studied anatomic function and obesity in postmenopausal women, reported that decreased sympathovagal activity with obesity in postmenopausal women. 13 Our study shows that, there is a similar enhanced risk of CVDs in post menopausal women, all the more with greater risk in the patients having diabetes as there is an established relation between Autonomic nervous system dysfunction in the form of heart rate variability and postural variations in blood pressure and cardiovascular events which cause high degree morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…ne of the problems faced by menopausal women is hypertension [2]. Hypertension is a major risk factor for cardiovascular diseases [4], and both healthy menopausal women and those with hypertension exhibit an imbalance in the autonomic control of the cardiovascular system, which may increase the risk of cardiovascular events [5]. Resting heart rate is a cardiac variable influenced by various factors, such as physical fitness level, body composition, age, the nervous system, and vascular structure and function [6].…”
Section: Introductionmentioning
confidence: 99%